2008
DOI: 10.1128/jb.00552-08
|View full text |Cite
|
Sign up to set email alerts
|

CcpN Controls Central Carbon Fluxes in Bacillus subtilis

Abstract: The transcriptional regulator CcpN of Bacillus subtilis has been recently characterized as a repressor of two gluconeogenic genes, gapB and pckA, and of a small noncoding regulatory RNA, sr1, involved in arginine catabolism. Deletion of ccpN impairs growth on glucose and strongly alters the distribution of intracellular fluxes, rerouting the main glucose catabolism from glycolysis to the pentose phosphate (PP) pathway. Using transcriptome analysis, we show that during growth on glucose, gapB and pckA are the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…2A and supplemental Table S2). Because these genes are normally fully repressed by CcpN in the presence of glucose during exponential growth (49,50), nitrogen starvation appears to alleviate glucose repression, despite the presence of high glucose concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…2A and supplemental Table S2). Because these genes are normally fully repressed by CcpN in the presence of glucose during exponential growth (49,50), nitrogen starvation appears to alleviate glucose repression, despite the presence of high glucose concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that ywjI constitutes with the upstream gene murAB an operon whose transcription does not depend on the glycolytic or neoglucogenic condition. Thus, like fbp, and contrary to the two other genes essential for gluconeogenesis, gapB and pckA, ywjI (glpX) is not regulated by CcpN (20,23).…”
mentioning
confidence: 99%
“…Indeed, the burst size scales with the lifetime of the active state of the operator, which for a self-repressed promoter, scales inversely with the concentration of repressor and is smaller under permissive conditions when the feedback is weak. In contrast to the strong transcriptional bursting observed for the glycolytic promoter, in the case of the gluconeogenic promoters, because derepression under glycolytic conditions greatly impairs growth (16,19), strict control by CcpN and limited noise are essential. Hence, the repressive mechanism of CcpN has evolved to limit bursting in the repressed state by impairing promoter escape by the RNAP, leading to very strong catabolite repression.…”
Section: Discussionmentioning
confidence: 99%
“…The operator site for CggR is located downstream of the transcription start site and upstream of the translation initiation region (RBS), and hence CggR is thought to function as a roadblock to the transcribing RNA Polymerase (RNAP) (17,18). The GapB and PckA enzymes are both required for the utilization of gluconeogenic carbon sources, such as malate, but their expression is deleterious under glycolytic regimes (15,16,19). CcpN is the repressor responsible for the very strong catabolite repression of the gapB and pckA promoters in the presence of glucose or other glycolytic substrates (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation